Legal Aspects of Consumer Protection in Indonesia - AnakA gungSagungNgurah Indradewi; I Nyoman Prabu Buana Rumiartha (International Journal of Psychosocial Rehabilitation, 2020)
The actions of the government in Indonesia in providing protection to consumers have been outlined in Law No. 8 of 1999 concerning Consumer Protection. In this era of free trade, special laws are needed that can regulate the security and safety of consumers.The legal aspects of consumer protection in Indonesia in this case consist of civil aspects, administrative aspects, and criminal aspects. That administrative law regulates the implementation of government functions in growing and improving the welfare of the general public is carried out by exercising the authority to guide and supervise various activities carried out by the community as stipulated in various laws and regulations in this case related to consumer protection. That this aspect of civilization is intended in all matters relating to civil rights and obligations of consumers. Some are considered important in the relationship of consumers and providers of goods and / or service providers (business actors). That the aspect of criminal law contained in the Criminal Code and Law Number 8 of 1999 concerning Consumer Protection, is an important source of consumer protection law.